FORMATION OF FOREIGN STUDENTS’ COMMUNICATIVE COMPETENCE WITHIN FOREIGN LANGUAGE ENVIRONMENT AS PART OF THE COURSE “LANGUAGE FOR PR” (EVIDENCE FROM THE LESSON “MARKET AND PRINCIPLES OF ITS FUNCTIONING”) - Fisenko, Olga; Karayel, Sevinc; Topbashoglu Eray, Keziban (Revista Inclusiones, 2020)
The main trend in teaching Russian as a foreign language is its focus on the development of communicative competence. This work, within a fragment of the manual Instruction of Professional Activity in Russian for Foreign Students of Public Relations (authors L.V. Adonina, S.V. Lazarev, S.V. Smirnova, O.S. Fisenko), presents instructional methods and techniques that allow to form communicative competencies as the proficiency in a foreign language in language classes for special purposes. The authors argue that the formation of communicative competence is the most important characteristic of a student speaking other language, which will allow him to further fulfill the need for communication in various fields of activity